Preparation method of ZIF-67-derived CoSe2-coated NC hollow nano cubic box material and ZIF-67-derived CoSe2-coated NC hollow nano cubic box material

By preparing ZIF-67-derived CoSe2@NC hollow nanocubic cell materials, the problems of pulverization and volume expansion of transition metal selenide materials during charge and discharge processes were solved, improving the cycle stability and electronic conductivity of sodium-ion batteries and enabling the application of high-capacity sodium-ion batteries.

CN119284844AInactive Publication Date: 2025-01-10BEIFANG UNIV OF NATITIES

Patent Information

Application Number
CN202411406728.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional transition metal selenide materials undergo pulverization and volume expansion during charging/discharging, leading to capacity decay and cycle stability issues, which limits their application in high-capacity, high-energy-density sodium-ion batteries.

Method used

The method for preparing ZIF-67-derived CoSe2@NC hollow nanocubic cell material involves forming a hollow structure through tannic acid etching, followed by heat treatment to form a hierarchical porous carbon matrix and embedded selenides, thus solving the problem of volume change during the charging and discharging process.

Benefits of technology

This improved the cycling stability and safety of the material, enhanced its electronic conductivity and ion diffusion capability, and enabled the fabrication of high-capacity, high-performance sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284844A_ABST
    Figure CN119284844A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage nano materials, and provides a ZIF-67-derived CoSe2-atNC hollow nano cubic box material and a preparation method thereof.The preparation method comprises the steps that a solution A is prepared from cobalt nitrate hexahydrate, cetyltrimethylammonium bromide and deionized water, a solution B is prepared from 2-methylimidazole and deionized water, and the ZIF-67-derived CoSe2-atNC hollow nano cubic box material is obtained; adding the solution A into the solution B, stirring to prepare a ZIF-67 precursor solution, and carrying out aging reaction to prepare a ZIF-67 nanocube material; preparing a solution C by adopting a ZIF-67 nanocube material and absolute ethyl alcohol, preparing a solution D by adopting tannic acid, deionized water and absolute ethyl alcohol, and adding the solution C into the solution D for etching reaction to prepare a TA-Co hollow nano cubic box material; carrying out first heat treatment on the TA-Co hollow nano cubic box material, mixing and grinding a product of the first heat treatment and selenium powder, and then carrying out second heat treatment to prepare the ZIF-67 derived CoSe2 (at) NC hollow nano cubic box material. The preparation method can be used for preparing the sodium battery negative electrode material with high specific capacity and high cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage nanomaterials, and in particular to a preparation method and material of a CoSe2@NC hollow nanocubic box material derived from ZIF-67. Background Art

[0002] In recent years, with the development of energy storage, metal organic framework structure sodium ion battery negative electrode materials have attracted much attention due to their excellent ion transport properties. Although various carbon-based materials have good electrical conductivity and structural stability, their adaptability development under high capacity and high energy density is limited, and they cannot meet large-scale applications such as electric vehicles.

[0003] At the same time, transition metal selenide materials are favored due to their characteristics in the Faraday charge transfer process. In this process, transition metal selenide materials show excellent electron transport and ion diffusion capabilities, and are expected to achieve ultra-high capacity and high energy density energy storage performance. However, the pulverization and volume expansion of traditional transition metal selenide materials during the charge / discharge process lead to capacity attenuation and cycle stability problems, which restrict their performance in practical applications.

[0004] Therefore, how to introduce the target material into the carbon matrix through effective structural design and composition optimization, provide an effective buffer matrix, alleviate the changes in volume and structure during the cycle, solve the pulverization and volume expansion problems of transition metal selenide materials during the charging / discharging process, and improve the material's cycle stability and safety, thereby promoting the development of high-capacity, high-performance sodium-ion battery technology, has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of this, in order to overcome the shortcomings of the prior art, the present invention aims to provide a preparation method and material of ZIF-67 derived CoSe2@NC hollow nanocubic box material.

[0006] According to a first aspect of the present invention, a method for preparing a ZIF-67 derived CoSe2@NC hollow nanocubic box material is provided, the method comprising: Step 1: Preparation of ZIF-67 (Zeolitic Imidazolate Framework-67) precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, solution B is prepared by using 2-methylimidazole and deionized water, and a ZIF-67 precursor solution is prepared by adding solution A to solution B with stirring; Step 2: Preparation of ZIF-67 nanocube material Performing an aging reaction on the prepared ZIF-67 precursor solution, separating, washing and drying the aging reaction product, and preparing a ZIF-67 nanocube material; Step 3: Preparation of TA-Co (tannic acid etched cobalt metal organic framework material) hollow nanocube box material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, solution D is prepared by using tannic acid, deionized water and anhydrous ethanol, solution C is added to solution D for etching reaction, and the etching reaction product is separated, cleaned and dried to prepare TA-Co hollow nanocube box material; Step 4: Preparation of ZIF-67 derived CoSe2@NC (nitrogen-carbon co-doped cobalt diselenide material) hollow nanocube box material The TA-Co hollow nanocube box material is subjected to a first heat treatment, and the product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0007] Preferably, the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention comprises, in step 1, preparing solution A using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and preparing solution B using 2-methylimidazole and deionized water, comprising: For every 1 mmol of cobalt nitrate hexahydrate, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared, and solution A is prepared using cobalt nitrate hexahydrate, the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; Prepare 70 mL of deionized water for every 55 mmol of 2-methylimidazole, and prepare solution B using 2-methylimidazole and the prepared deionized water according to the ratio.

[0008] Preferably, the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention, in step one, a ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring, comprising: adding 1 volume part of solution A to 7 volume parts of solution B according to a ratio and stirring at room temperature for 0.5h to prepare a ZIF-67 precursor solution.

[0009] Preferably, in the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocube box material of the present invention, in step 2, the prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried to obtain the ZIF-67 nanocube material, including: aging the prepared ZIF-67 precursor solution at room temperature for 0.5 h, centrifuging the aging reaction product and then cleaning it with anhydrous ethanol, and drying the cleaned product at 80°C for 10 h to obtain the ZIF-67 nanocube material.

[0010] Preferably, the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocube box material of the present invention comprises, in step 3, preparing solution C using ZIF-67 nanocube material and anhydrous ethanol, and preparing solution D using tannic acid, deionized water and anhydrous ethanol, comprising: Solution C was prepared by dispersing 500 mg of ZIF-67 nanocube material into 20 mL of anhydrous ethanol; Solution D was prepared by dissolving 300 mg of tannic acid in 300 mL of a mixed solvent, wherein the mixed solvent was prepared from anhydrous ethanol and deionized water in a volume ratio of 1:1.

[0011] Preferably, the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention, in step three, by adding solution C to solution D for etching reaction, separating, cleaning and drying the etching reaction product, to obtain TA-Co hollow nanocubic box material, including: adding 1 volume part of solution C to 15 volume parts of solution D according to the ratio, stirring for 10 minutes, centrifuging the etching reaction product and then cleaning it with anhydrous ethanol, and drying the cleaned product at 80°C for 10 hours to obtain TA-Co hollow nanocubic box material.

[0012] Preferably, in the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention, in step four, the TA-Co hollow nanocubic box material is subjected to a first heat treatment, including: placing the TA-Co hollow nanocubic box material in an inert gas environment, heating the temperature to 600°C-800°C at a heating rate of 2-5°C / min, then keeping the temperature for 2 hours, and naturally cooling to room temperature.

[0013] Preferably, in the method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention, the inert gas environment is composed of argon gas with a flow rate of 25 mL / min.

[0014] Preferably, in the preparation method of the ZIF-67-derived CoSe2@NC hollow nanocubic box material of the present invention, in step four, the product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment, comprising: mixing and grinding the product of the first heat treatment with selenium powder in a weight ratio of 1:1, placing the ground product in an inert gas environment, heating it to 450°C at a heating rate of 2-5°C / min, keeping it warm for 2h, and naturally cooling it to room temperature.

[0015] According to a second aspect of the present invention, a ZIF-67-derived CoSe2@NC hollow nanocubic box material is provided. The ZIF-67-derived CoSe2@NC hollow nanocubic box material is prepared according to the above method.

[0016] The preparation method and material of the CoSe2@NC hollow nanocubic box material derived from ZIF-67 of the present invention have the following beneficial technical effects: 1. By etching ZIF-67 with tannic acid to convert it into a hollow structure, the problems of pulverization and volume expansion of transition metal selenide materials during the charging / discharging process are solved, the cycle stability and safety of the material are improved, and it is conducive to the preparation of high-capacity, high-performance sodium-ion batteries.

[0017] 2. Through the first heat treatment, the organic ligands are converted into carbon materials to form a carbon matrix with a hierarchical porous structure, which significantly increases the specific surface area of ​​the material and enhances its electronic conductivity; provides abundant electrochemically active interface sites, good mechanical strength, and effectively alleviates the volume change of the material, so that the material exhibits excellent sodium storage performance closely related to specific capacity and long cycle life at high current density.

[0018] 3. Through the second heat treatment, selenium element is introduced to form metal selenide, and the target material is introduced into the carbon matrix. Compared with metal oxides and metal sulfides, transition metal selenide materials exhibit excellent electron transport and ion diffusion capabilities.

[0019] 4. Deionized water was used as solvent to prepare ZIF-67, which is non-toxic and environmentally friendly; TA-Co hollow nanoboxes were obtained by etching with tannic acid, which significantly improved the simplicity of the process and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 1 of the present invention, wherein: Figure 1 (a) The magnification is 20,000 times. Figure 1 (b) Magnification is 100,000 times; Figure 2 This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 2 of the present invention, wherein: Figure 2 (a) The magnification is 20,000 times. Figure 2 (b) Magnification is 100,000 times; Figure 3 This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 3 of the present invention, wherein: Figure 3 (a) The magnification is 20,000 times. Figure 3 (b) Magnification is 100,000 times; Figure 4 This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 4 of the present invention, wherein: Figure 4 (a) The magnification is 20,000 times. Figure 4 (b) Magnification is 100,000 times; Figure 5 This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 5 of the present invention, wherein: Figure 5 (a) The magnification is 20,000 times. Figure 5 (b) Magnification is 100,000 times; Figure 6 This is a FESEM image of the ZIF-67 nanocube prepared in Example 5 of the present invention, wherein: Figure 6 (a) The magnification is 50,000 times. Figure 6 (b) Magnification is 100,000 times; Figure 7 This is a TEM image of the TA-Co hollow nanocube box material prepared in Example 5 of the present invention after the first heat treatment, wherein: Figure 7 (a) The magnification is 25,000 times. Figure 7 (b) Magnification is 30,000 times; Figure 8 This is a TEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 5 of the present invention, wherein: Figure 8 (a) The magnification is 25,000 times. Figure 8 (b) Magnification is 30,000 times; Fig. 9This is a FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 6 of the present invention, wherein: Fig. 9 (a) The magnification is 20,000 times. Fig. 9 (b) Magnification is 100,000 times; Fig.10 XRD patterns of the ZIF-67-derived CoSe2@NC hollow nanocube box materials prepared in Examples 4, 5, and 6 of the present invention; Fig.11 XRD patterns of the ZIF-67 nanocube material and the TA-Co hollow nanocube box material prepared in Example 5 of the present invention; Fig.12 The rate performance diagram of the CoSe2@NC hollow nanocube box material derived from ZIF-67 prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 of the present invention; Fig.13 This is a charge-discharge curve diagram of the first five cycles of the ZIF-67-derived CoSe2@NC hollow nanocube material prepared in Example 5 of the present invention at a current density of 0.05 A / g. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0023] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0024] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0025] Example 1 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0026] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 800° C. at a heating rate of 5° C. / min, then kept at that temperature for 2 h, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 5°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0027] Example 2 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0028] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 700° C. at a heating rate of 5° C. / min, then kept at this temperature for 2 hours, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 5°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0029] Example 3 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0030] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 600° C. at a heating rate of 5° C. / min, then kept at this temperature for 2 hours, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 5°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0031] Example 4 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0032] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 600° C. at a heating rate of 2° C. / min, then kept at this temperature for 2 h, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 2°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0033] Example 5 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0034] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 700° C. at a heating rate of 2° C. / min, then kept at this temperature for 2 h, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 2°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0035] Example 6 A preparation method of CoSe2@NC hollow nanocubic box material derived from ZIF-67: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water. Specifically, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared for every 1 mmol of cobalt nitrate hexahydrate, and solution A is prepared by using cobalt nitrate hexahydrate and the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; 70 mL of deionized water is prepared for every 55 mmol of 2-methylimidazole, and solution B is prepared by using 2-methylimidazole and the prepared deionized water according to the ratio; A ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring. Specifically, 1 volume part of solution A is added to 7 volume parts of solution B according to a ratio and stirred at room temperature for 0.5 h to prepare a ZIF-67 precursor solution; Step 2: Preparation of ZIF-67 nanocube material The prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried. Specifically, the prepared ZIF-67 precursor solution is subjected to an aging reaction at room temperature for 0.5 h, the aging reaction product is centrifuged and then cleaned with anhydrous ethanol, and the cleaned product is dried at a temperature of 80° C. for 10 h to obtain a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, and solution D is prepared by using tannic acid, deionized water and anhydrous ethanol. Specifically, 500 mg of ZIF-67 nanocube material is dispersed in 20 mL of anhydrous ethanol to prepare solution C; 300 mg of tannic acid is dissolved in 300 mL of a mixed solvent prepared by anhydrous ethanol and deionized water in a volume ratio of 1:1 to prepare solution D; Solution C was added to solution D for etching reaction, and the etching reaction product was separated, cleaned and dried. 1 volume of solution C was added to 15 volume of solution D according to the ratio, stirred for 10 minutes, and the etching reaction product was centrifuged and cleaned with anhydrous ethanol. The cleaned product was dried at 80°C for 10 hours to obtain TA-Co hollow nanocube box material.

[0036] Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment. Specifically, the TA-Co hollow nanocube box material is placed in an inert gas environment consisting of argon gas with a flow rate of 25 mL / min, heated to 800° C. at a heating rate of 2° C. / min, then kept at that temperature for 2 h, and naturally cooled to room temperature; The product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment. Specifically, the product of the first heat treatment is mixed and ground with selenium powder in a weight ratio of 1:1. The ground product is placed in an inert gas environment, heated to 450°C at a heating rate of 2°C / min, kept warm for 2h, and naturally cooled to room temperature to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0037] Example 7 The microstructure of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 was observed using a thermal field emission scanning electron microscope (FESEM) of model SIGMA 500 produced by Zeiss, Germany. For the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 5, the experimental process and test parameters include: the material is evenly dispersed on the conductive glue, and is pasted on the sample stage for observation using the instrument, and the acceleration voltage is 5kV. The FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocubic box material prepared in Example 1 is shown in FIG. Figure 1 ,in, Figure 1 (a) The magnification is 20,000 times. Figure 1 (b) The magnification is 100,000 times; FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube material prepared in Example 2 is shown in Figure 2 ,in, Figure 2 (a) The magnification is 20,000 times. Figure 2 (b) The magnification is 100,000 times; FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 3 is shown in Figure 3 ,in, Figure 3 (a) The magnification is 20,000 times. Figure 3 (b) The magnification is 100,000 times; FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 4 is shown in Figure 4 ,in, Figure 4 (a) The magnification is 20,000 times. Figure 4 (b) The magnification is 100,000 times; FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube material prepared in Example 5 is shown in Figure 5 ,in, Figure 5 (a) The magnification is 20,000 times. Figure 5 (b) The magnification is 100,000 times; the FESEM image of the ZIF-67 nanocube prepared in Example 5 is shown in Figure 6 ,in, Figure 6 (a) The magnification is 50,000 times. Figure 6 (b) The magnification is 100,000 times; FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube material prepared in Example 6 is shown in Fig. 9 ,in, Fig. 9 (a) The magnification is 20,000 times. Fig. 9 (b) Magnification is 100,000 times.

[0038] Figure 1This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 1. Figure 1 As shown, the ZIF-67-derived CoSe2@NC hollow nanocubic box material presents a cubic morphology, is evenly dispersed, and the CoSe2 particles are embedded in the carbon skeleton; the ZIF-67-derived CoSe2@NC hollow nanocubic box material, as a sodium ion battery electrode material, provides active sites for redox reactions, thereby improving electronic conductivity and ultimately obtaining a high specific capacity.

[0039] Figure 2 This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 2. Figure 2 As shown in the figure, the ZIF-67-derived CoSe2@NC hollow nanocubic box material presents a cubic morphology. As the temperature of the first heat treatment increases, the carbon skeleton becomes more uniform, and the CoSe2 particles are embedded in the carbon skeleton. As an electrode material for sodium ion batteries, the ZIF-67-derived CoSe2@NC hollow nanocubic box material provides more active sites for redox reactions, thereby improving electronic conductivity, and ultimately obtaining a high specific capacity and a uniform carbon skeleton that can alleviate the volume expansion and electrode pulverization that occur during the redox reaction.

[0040] Figure 3 This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 3. Figure 3 As shown, the ZIF-67-derived CoSe2@NC hollow nanocubic box material presents a cubic morphology, and the CoSe2 particles are embedded in the carbon skeleton; the ZIF-67-derived CoSe2@NC hollow nanocubic box material, as a sodium ion battery electrode material, provides more active sites for redox reactions, thereby improving electronic conductivity and ultimately obtaining a high specific capacity.

[0041] Figure 4 This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 4. Figure 4 As shown, the ZIF-67-derived CoSe2@NC hollow nanocube box material presents a cubic morphology and is evenly dispersed, with CoSe2 particles embedded in the carbon skeleton; as the heating rate decreases, the CoSe2 nanoparticles become more uniform. The ZIF-67-derived CoSe2@NC hollow nanocube box material, as an electrode material for sodium ion batteries, is beneficial to the formation of a solid electrolyte (SEI) film during the first charge and discharge process of the battery, thereby improving the electronic conductivity and ultimately obtaining a higher specific capacity.

[0042] Figure 5This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube material prepared in Example 5. Figure 5 As shown in the figure, the ZIF-67-derived CoSe2@NC hollow nanocubic box material presents a cubic morphology, and the CoSe2 particles are embedded in the carbon skeleton; with the decrease of the heating rate, the distribution of the CoSe2 nanoparticles is more uniform, and with the increase of the temperature of the first heat treatment, the ZIF-67-derived CoSe2@NC hollow nanocubic box material is more evenly dispersed. As an electrode material for sodium ion batteries, it provides more active sites for redox reactions, thereby improving the electronic conductivity and ultimately obtaining a higher specific capacity. The carbon skeleton can alleviate the volume expansion and electrode pulverization that occur during the reaction.

[0043] Figure 6 The FESEM image of the ZIF-67 nanocube prepared in Example 5 is as follows: Figure 6 As shown, the prepared ZIF-67 nanocube material has a cubic morphology and a smooth surface, providing an excellent template for the ZIF-67-derived CoSe2@NC hollow nanocube box material.

[0044] The morphology and structure of the TA-Co hollow nanocube box material prepared in Example 5 and the CoSe2@NC hollow nanocube box material derived from ZIF-67 in Example 5 were characterized by a transmission electron microscope (TEM, JEM-2100F, JEOL, Japan). The experimental process is: the material is dispersed in an ethanol solution, dripped on a copper mesh and observed using an instrument. The TEM image of the TA-Co hollow nanocube box material prepared in Example 5 after the first heat treatment is shown in FIG. Figure 7 ,in, Figure 7 (a) The magnification is 25,000 times. Figure 7 (b) The magnification is 30,000 times; the TEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 5 is shown in Figure 8 ,in, Figure 8 (a) The magnification is 25,000 times. Figure 8 (b) Magnification is 30,000 times; Figure 7 This is a TEM image of the TA-Co hollow nanocube box material prepared in Example 5 after the first heat treatment. Figure 7 As shown, the Co element is uniformly embedded in the TA-Co hollow nanocubic box material; Figure 8 TEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 5, as shown in Figure 8 As shown, CoSe2 particles are uniformly embedded in the ZIF-67 derived CoSe2@NC hollow nanocubic box material.

[0045] Fig. 9 This is the FESEM image of the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 6. Fig. 9 As shown, the ZIF-67-derived CoSe2@NC hollow nanocube box material presents a cubic morphology, and the CoSe2 particles are embedded in the carbon skeleton; as the heating rate decreases, the volume of the CoSe2 nanoparticles becomes more uniform. As a sodium ion battery electrode material, it provides more active sites for redox reactions, thereby improving electronic conductivity and ultimately obtaining a high specific capacity.

[0046] The X-ray diffractometer (XRD) of model XRD-6000 (3KW) produced by Shimadzu Corporation of Japan was used to analyze the phase composition of the ZIF-67-derived CoSe2@NC hollow nanocube box materials prepared in Examples 4, 5, and 6, and the ZIF-67 nanocube material and TA-Co hollow nanocube box material prepared in Example 5; the test process and test parameter settings include: placing the material in a groove (2.0*2.0cm) of a glass slide, preferably just filling the groove, and then placing it in an X-ray diffractometer, the ray source is Cu target Kα ray (λ=0.15418nm), the scanning range is 5-80°, the scanning rate is 5° / min, the tube voltage is 40kV, the tube current is 30mA, and the test results are shown in Fig.10 and Fig.11 .

[0047] Fig.10 The X-ray diffraction analysis diagram of the CoSe2@NC hollow nanocube box material derived from ZIF-67 prepared in Example 4, Example 5, and Example 6 of the present invention is as follows: Fig.10 As shown, the characteristic peaks of Example 4, Example 5, and Example 6 correspond to standard card #53-449 and standard card #65-3327, indicating that the CoSe2@NC hollow nanocube material was synthesized.

[0048] Fig.11 The X-ray diffraction analysis diagram of the ZIF-67 nanocube material and the TA-Co hollow nanocube box material prepared in Example 5 of the present invention is as follows: Fig.11 As shown, the XRD patterns of the TA-Co hollow nanocube box material obtained after tannic acid etching correspond well to those of the ZIF-67 nanocube material, indicating that the TA-Co hollow nanocube box material inherits the metal organic framework structure of the ZIF-67 nanocube material.

[0049] The ZIF-67 derived CoSe2@NC hollow nanocubic box materials in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 were uniformly mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1 and dissolved in 1-methyl-2-pyrrolidine (NMP) to form a slurry, which was then coated on a copper foil current collector and dried in a vacuum drying oven at 60°C for 24 hours. The ZIF-67 derived CoSe2@NC hollow nanocubic box material electrodes prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 were cut using a tablet press machine of model SZ-50-14 produced by Shenzhen Kejing Material Technology Co., Ltd. The test process and test parameters include: the materials prepared in each comparative example and each example were cut into discs with a diameter of 12 mm as electrode materials for standby use, and CR2025 battery shells, 1M NaCF3SO3in were used. DIGLYME (100%) electrolyte, glass fiber diaphragm and metal sodium sheet were placed together in a glove box with a water and oxygen content of less than 0.1ppm. The electrode material was placed in the center of the positive electrode shell, and two drops of electrolyte were added to fully infiltrate the electrode material. Then, the diaphragm was covered on the electrode plate with tweezers, and the metal sodium sheet, gasket, shrapnel and negative electrode shell were placed in sequence. Finally, the battery was sealed with a battery sealing machine model PX-HS-20 produced by Shenzhen Kejing Material Technology Co., Ltd. The assembled battery was left to stand for 12 hours before the electrochemical performance test.

[0050] The half-cells assembled from the ZIF-67-derived CoSe2@NC hollow nanocubic box materials prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 were electrochemically tested using a Blue Electric Battery Test System model CT3002A produced by Wuhan Blue Electric Electronics Co., Ltd. The test process and test parameters included: taking current densities of 0.05A / g, 0.1A / g, 0.2A / g, 0.5A / g and 1.0A / g, 2.0A / g, 5.0A / g, 10.0A / g, and 0.05A / g to compare the electrochemical performance of each example through constant current charge and discharge tests, as shown in FIG. Fig.12 and Fig.13 shown.

[0051] Fig.12 The rate performance diagram of the CoSe2@NC hollow nanocube box material derived from ZIF-67 prepared in Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6 of the present invention is as follows: Fig.12 As shown, the half-cell assembled from the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 5 has good rate performance and high first coulombic efficiency, and has a high overlap of charge and discharge capacity at different current densities, and its efficiency is maintained at about 99%.

[0052] Fig.13 The first five charge and discharge curves of the half-cell assembled with the ZIF-67-derived CoSe2@NC hollow nanocube box material prepared in Example 5 of the present invention at a current density of 0.05 A / g, wherein the first-cycle charge capacity is 580.66 mAh / g, the discharge capacity is 661.09 mAh / g, and the first-cycle efficiency is as high as 87.8%.

[0053] The preparation method and material of the CoSe2@NC hollow nanocubic box material derived from ZIF-67 of the present invention have the following beneficial technical effects: 1. By etching ZIF-67 with tannic acid to convert it into a hollow structure, the problems of pulverization and volume expansion of transition metal selenide materials during the charging / discharging process are solved, the cycle stability and safety of the material are improved, and it is conducive to the preparation of high-capacity, high-performance sodium-ion batteries.

[0054] 2. Through the first heat treatment, the organic ligands are converted into carbon materials to form a carbon matrix with a hierarchical porous structure, which significantly increases the specific surface area of ​​the material and enhances its electronic conductivity; provides abundant electrochemically active interface sites, good mechanical strength, and effectively alleviates the volume change of the material, so that the material exhibits excellent sodium storage performance closely related to specific capacity and long cycle life at high current density.

[0055] 3. Through the second heat treatment, selenium element is introduced to form metal selenide, and the target material is introduced into the carbon matrix. Compared with metal oxides and metal sulfides, transition metal selenide materials exhibit excellent electron transport and ion diffusion capabilities.

[0056] 4. Deionized water was used as solvent to prepare ZIF-67, which is non-toxic and environmentally friendly; TA-Co hollow nanoboxes were obtained by etching with tannic acid, which significantly improved the simplicity of the process and is suitable for industrial promotion and application.

[0057] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a ZIF-67 derived CoSe2@NC hollow nanocubic box material, characterized in that: The method comprises: Step 1: Preparation of ZIF-67 precursor solution Solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, solution B is prepared by using 2-methylimidazole and deionized water, and a ZIF-67 precursor solution is prepared by adding solution A to solution B with stirring; Step 2: Preparation of ZIF-67 nanocube material Performing an aging reaction on the prepared ZIF-67 precursor solution, separating, washing and drying the aging reaction product, and preparing a ZIF-67 nanocube material; Step 3: Preparation of TA-Co hollow nanocube material Solution C is prepared by using ZIF-67 nanocube material and anhydrous ethanol, solution D is prepared by using tannic acid, deionized water and anhydrous ethanol, solution C is added to solution D for etching reaction, and the etching reaction product is separated, cleaned and dried to prepare TA-Co hollow nanocube box material; Step 4: Preparation of ZIF-67-derived CoSe2@NC hollow nanocube materials The TA-Co hollow nanocube box material is subjected to a first heat treatment, and the product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment to obtain a ZIF-67-derived CoSe2@NC hollow nanocube box material.

2. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step 1, solution A is prepared by using cobalt nitrate hexahydrate, hexadecyltrimethylammonium bromide and deionized water, and solution B is prepared by using 2-methylimidazole and deionized water, comprising: For every 1 mmol of cobalt nitrate hexahydrate, 4 mg of hexadecyltrimethylammonium bromide and 10 mL of deionized water are prepared, and solution A is prepared using cobalt nitrate hexahydrate, the prepared hexadecyltrimethylammonium bromide and deionized water according to the ratio; Prepare 70 mL of deionized water for every 55 mmol of 2-methylimidazole, and prepare solution B using 2-methylimidazole and the prepared deionized water according to the ratio.

3. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step 1, a ZIF-67 precursor solution is prepared by adding solution A to solution B and stirring, including: adding 1 volume part of solution A to 7 volume parts of solution B according to a ratio and stirring at room temperature for 0.5h to prepare a ZIF-67 precursor solution.

4. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step 2, the prepared ZIF-67 precursor solution is subjected to an aging reaction, and the aging reaction product is separated, cleaned and dried to obtain a ZIF-67 nanocube material, including: aging the prepared ZIF-67 precursor solution at room temperature for 0.5 hours, centrifuging the aging reaction product and then cleaning it with anhydrous ethanol, and drying the cleaned product at 80°C for 10 hours to obtain a ZIF-67 nanocube material.

5. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step 3, a solution C is prepared using ZIF-67 nanocube material and anhydrous ethanol, and a solution D is prepared using tannic acid, deionized water and anhydrous ethanol, comprising: Solution C was prepared by dispersing 500 mg of ZIF-67 nanocube material into 20 mL of anhydrous ethanol; Solution D was prepared by dissolving 300 mg of tannic acid in 300 mL of a mixed solvent, wherein the mixed solvent was prepared from anhydrous ethanol and deionized water in a volume ratio of 1:

1.

6. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step three, solution C is added to solution D for etching reaction, and the etching reaction product is separated, cleaned and dried to obtain a TA-Co hollow nanocubic box material, including: adding 1 volume part of solution C to 15 volume parts of solution D according to the ratio, stirring for 10 minutes, centrifuging the etching reaction product and then cleaning it with anhydrous ethanol, and drying the cleaned product at 80°C for 10 hours to obtain a TA-Co hollow nanocubic box material.

7. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step 4, the TA-Co hollow nanocube box material is subjected to a first heat treatment, including: placing the TA-Co hollow nanocube box material in an inert gas environment, heating the temperature to 600°C-800°C at a heating rate of 2-5°C / min, then keeping the temperature for 2 hours, and naturally cooling to room temperature.

8. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 7, characterized in that: The inert gas environment consisted of argon at a flow rate of 25 mL / min.

9. The method for preparing the ZIF-67-derived CoSe2@NC hollow nanocubic box material according to claim 1, characterized in that: In step four, the product of the first heat treatment is mixed and ground with selenium powder and then subjected to a second heat treatment, including: mixing and grinding the product of the first heat treatment with selenium powder in a weight ratio of 1:1, placing the ground product in an inert gas environment, heating it to 450°C at a heating rate of 2-5°C / min, keeping it warm for 2h, and naturally cooling it to room temperature.

10. A ZIF-67 derived CoSe2@NC hollow nanocubic box material, characterized in that: The ZIF-67 derived CoSe2@NC hollow nanocube material is prepared according to any one of claims 1-9.

Citation Information

Patent Citations

  • CoSe2 / hollow carbon nanosphere / S composite lithium-sulfur battery positive electrode material and preparation method thereof

    CN111540888A

  • Cobalt nickel selenide nitrogen-doped amorphous carbon nano composite negative electrode material as well as preparation and application thereof

    CN111554896A

  • Cobalt diselenide@porous nitrogen-doped carbon nano composite material, potassium ion battery and preparation method thereof

    CN113410440A

  • Hollow nano selenide as well as preparation method and application thereof

    CN113964317A

  • Cobalt-iron alloy nanoparticles based on hollow cubic carbon material as well as preparation method and application of cobalt-iron alloy nanoparticles

    CN114256470A

Cited By

  • Sulfur-doped C3N4-CoSe2 lithium-sulfur battery positive electrode catalyst as well as preparation method and application thereof

    CN121054676A

  • Synthesis of multi-metallic nanoparticle carbon materials from zeolitic imidazolate frameworks (ZIFS)

    WO2025144282A1

  • Synthesis of metal selenide-carbon materials from MOF based materials

    WO2025144283A1